STRATEGI PENINGKATAN KUALITAS PELAYANAN BERBASIS SWOT PADA KANTOR PELAYANAN PAJAK PRATAMA SEMARANG CANDISARI - Aslichatul Jannah; Agus Suratno; Endang Sulistiyani (Politeknik Negeri Semarang, 2017)
Service quality is very important for a company. In the process of improving the service quality, Pratama Semarang Candisari Tax Office requires strategy. The objective of this study is to define the appropriate strategy to improve service quality of Pratama Semarang Candisari Tax Office by applying SWOT analysis. Pratama Semarang Candisari Tax Office, a public service agency under the Ministry of Finance is in charge of serving the community in extending taxation liabilities. The population used is the taxpayers and employees of the Pratama Semarang Candisari Tax Office, while the sample used is 100 taxpayers and 36 employees of service parts and Account Representative of Pratama Semarang Candisari Tax Office. The collection of data was done by observation, questionnaires, interviews, and literature, while the sampling technique used is incidental sampling for taxpayers and purposive sampling for employees of the Pratama Semarang Candisari Tax Office. The results show that Pratama Semarang Candisari Tax Office in the position of the quadrant 1, it is shown on the coordinates of the x = 0.30 and y = 0.71. It means that the company is suggested to employ strategy of concentration. It may also use the Strengths Opportunities Strategy, Weaknesses Opportunities Strategy, Strength Threats Strategy and Weaknesses ThreatsStrategy.